PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA E-BOOKLET TERHADAP PENGETAHUAN AKSEPTOR TENTANG KEPUTIHAN PADA KB SUNTIK - Qudratullah, Fyzria; Ria Gustiani; Dona Tri Sundari (LPPM STIKes Mitra Adiguna, 2024)
Health education is an effort to provide psychological conditions and targets so that they behave in accordance with the demands of health values ??so that it can influence health behavior as a medium-term result of increasing health indicators in individuals as an outcome. One of the delivery efforts is using health education media, namely e-Bokklet, so that targets can increase their knowledge, which is then expected to lead to changes in behavior in a positive direction in the health sector. The aim of this research is to determine the effect of health education using e-booklet media on acceptors' knowledge about vaginal discharge during injectable birth control at PMB Misni Herawati. This research is a type of quantitative research with a pre-experimental research design using a one-group pretest-posttest design method. This research was carried out at PMB Misni Herawati on 09 October - 09 November 2023. The sample in this study was 82 samples using a purposive sampling technique. Data analysis used the Wilcoxon Test. The research results obtained with a value of ?=0.000 <0.05, which means there is an influence of knowledge about vaginal discharge before and after receiving health education using e-booklet media. With the results of this research, it is hoped that mothers who accept family planning, especially injectable family planning, will always increase their knowledge from any media related to reproductive health so that it can be prevented as early as possible if there are signs that they experience. Keywords: health education, e-booklet media, knowledge, vaginal discharge